Profiles of Physical Function, Physical Activity, and Sedentary Behavior and their Associations with Mental Health in Residents of Assisted Living Facilities - Park, S.; Thogersen-Ntoumani, Cecilie; Ntoumanis, Nikos; Stenling, A.; Fenton, S.; Veldhuijzen van Zanten, J. (Wiley-Blackwell Publishing, 2017)
Background: The current study used latent profile analyses to identify classes of older participants based on physical health, physical function, light physical activity, moderate-to-vigorous physical activity, and sedentary behavior, and then examined differences in mental health between these classes. Methods: Eighty-five residents (M = 77.5 years old, SD = 8.2) from assisted living facilities participated. Light physical activity, moderate-to-vigorous physical activity, and sedentary behavior were assessed by accelerometers, physical function was measured using different tasks (mobility, grip strength, and spirometry), and body mass index was calculated. Mental and physical health (i.e. anxiety, depression, fatigue, vitality, and subjective mental and physical health) were assessed by questionnaires. Results: Latent profile analyses revealed three classes: “Class 1: Low physical function and physical activity with a highly sedentary lifestyle” (27.1%), “Class 2: Moderate physical function and physical activity with a moderate sedentary lifestyle” (41.2%), “Class 3: High physical function and physical activity with an active lifestyle” (31.8%). The results revealed that the latter class reported better mental health than the other two classes. Conclusions: This study suggests that health promotion for older adults might benefit from identifying profiles of movement-related behaviors when examining the links between physical activity and mental health. Future study should test the intervention potential of this profiling approach.